Market Arrivals and Price Trend of Important Fruits at Azadpur Mandi, Delhi - Godara, C. P.; Bhonde, S. R. (Indian Journal of Marketing, 2006)
Fruit production is one of the most important sources of income and their production as such occupies an important place in the agricultural development and economy of the country. Delhi is the leading state and in fruits marketing and consumption Delhi Azadpur Mandi has maximum potential for fruits marketing. The present study was under taken to examine the arrivals and prices of selected major fruits in Agriculture Produce Market Committee, Azadpur for the period of 3 years i.e. from 2003-04 to 2005-06. The secondary data collected from APMC Azadpur Delhi for 7 major fruits viz. apple, banana, lemon, mango, mosambi, orange and papaya were analyzed to study the growth rate of arrivals and prices as well as seasonal fluctuations. The movement of arrivals and prices were worked out with the help of seasonal index. The study reveals that, the prices of all fruits increased with decreasing arrivals in market. The study of seasonal fluctuations in arrivals and prices showed that arrivals of most of the fruits were higher in the peak season of crop and lower in the lean season. The maximum arrivals were for apples followed by mango and orange during all three years of study. The correlation between arrivals and prices were worked out and found that these are negatively correlated for all fruits. When arrival of fruits increase prices decreased and vice-versa